Macrowear effects of external quartz abrasives of different size and concentration in rabbits (Oryctolagus cuniculus). Issue 8 (23rd November 2021) - Martin, Louise F.; Ackermans, Nicole L.; Richter, Henning; Kircher, Patrick; Hummel, Jürgen; Codron, Daryl; Clauss, Marcus; Hatt, Jean‐Michel
Abstract: External quartz abrasives are one of the driving forces of macrowear in herbivorous animals. We tested to what extent different sizes and concentrations influence their effect on tooth wear. We fed seven pelleted diets varying only in quartz concentration (0%, 4%, and 8%) and size (fine silt: ∼4 μm, coarse silt: ∼50 μm, fine sand: ∼130 μm) to rabbits ( Oryctolagus cuniculus, n = 16) for 2 weeks each in a randomized serial experiment. Measurements to quantify wear and growth of incisors and the mandibular first cheek tooth, as well as heights of all other cheek teeth, were performed using calipers, endoscopic examination, and computed tomography scans before and after each feeding period. Tooth growth showed a compensatory correlation with wear. Absolute tooth height (ATH) and relative tooth height (RTH); relative to the 0% quartz "control" diet) was generally lower on the higher concentration and the larger size of abrasives. The effect was more pronounced on the maxillary teeth, on specific tooth positions and the right jaw side. When offered the choice between different sizes of abrasives, the rabbits favored the silt diets over the control and the fine sand diet; in a second choice experiment with different diets, they selected a pelleted diet with coarse‐grained sand, however. This study confirms the dose‐ and size‐dependent wear effects of external abrasives, and that hypselodont teeth show compensatory growth. The avoidance of wear did not seem a priority for animals with hypselodont teeth, since the rabbits did not avoid diets inducing a certain degree of wear. Abstract : Absolute tooth height (in mm) for maxillary cheek teeth of rabbits ( Oryctolagus cuniculus, n = 16) fed lucerne based pelleted control diet or the same with added 8% of fine silt, coarse silt or fine sand for 14 days each in a serial feeding experiment (see also Figure 3e). Research Highlights: Exposure of rabbit teeth to external quartz abrasives results in distinct macrowear patterns depending on the size and concentration they are fed in as well as tooth position. The rabbits prefer the quartz enriched to control diets especially at when silt or coarse sand is added, but the higher wear rates induced by these abrasives are eventually compensated by regrowth of the hypselodont dentition.